Peran Otoritas Jasa Keuangan Dalam Pengawasan Kesehatan Perbankan Di Indonesia - Miftakhul Huda (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
This study aims to describe the role of the Financial Services Authority (OJK) in banking health supervision in Indonesia. The Financial Services Authority was formed with the aim that all financial service activities within the financial services sector be carried out in an orderly, fair, transparent and accountable manner, and be able to realize a financial system that grows in a sustainable and stable manner, and is able to protect the interests of consumers and the public. OJK supervision consists of indirect supervision (off site supervision) and direct supervision (on site examination). The level of bank supervision by the Financial Services Authority (OJK) includes normal supervision, intensive supervision, and special supervision.